Estudo preditivo da sobrevivência e crescimento de bactérias patogênicas em queijo de coalho - Araújo, Valdenice Gomes de (2016)
Minimally ripened cheeses, a category that includes the coalho cheese, have physicochemical characteristics that facilitate the survival and growth of pathogenic bacteria associated with foodborne illness outbreaks. Use of mathematical models in the predictive microbiology allows to estimate the effect of biotic and abiotic conditions on microbial growth, and hence the possible risk associated with the presence and increase of the population of a specific pathogen in a particular food. Considering these aspects, the present study aimed to: (i) assess the coalho cheese as a potential substrate for the growth of the pathogenic bacteria Escherichia coli, Listeria monocytogenes, Staphylococcus aureus and Salmonella spp. in function of temperature, pH and water activity (aw) found in commercial samples of this type of product; and (ii) performing primary modeling growth of different strains of E. coli in coalho cheese samples stored under low temperature. The estimates of the growth kinetics parameter (maximum growth rate - Grmax, log UFC/g/h) in function of the combination of the values (percentile 20, 50, 75 and 90) for temperature, pH and aw were generated by ComBase Predictor. The growth kinetics (Grmax) of E. coli strains in coalho cheese (10 °C) was assessed by using the primary model of Baranyi and Roberts (1994), available in spreadsheet DMFit 3.5 (ComBase). The largest Grmax values as a function of different combinations of temperature, pH and aw were observed for L. monocytogenes (Grmax 0.01 to 0.07 log CFU/g/h), Salmonella (Grmax 0.01 to 0.04 log CFU/g/h) and S. aureus (Grmax <0.01 to 0.05 log CFU/g/h). E. coli Grmax values varied from 0.01 to 0.03 log CFU/g/h. Overall, the Grmax values increased as the temperature increased in cheese samples, regardless of the aw and pH values. The estimated Grmax values for the E. coli strains when inoculated into coalho cheese ranged from 0.01 to 0.03 log CFU/g/h, respectively. High R2 values (≥ 0.97) were obtained to the growth curves of all E. coli strains tested. The estimates of the growth kinetics parameters in function of the values of temperature, aw and pH tested, as well as those observed in artificially contaminaed cheese samples showed that the coalho cheese is characterized as favorable substrate for the survival and growth of E. coli, L. monocytogenes, Salmonella spp. and S. aureus, which may pose a risk to consumers’ health if contaminated with these bacteria during production, transportation or marketing.